Nitrate transport and signalling in Arabidopsis - Krapp, Anne (Journal of experimental botany, 2014)
Plants have developed adaptive responses allowing them to cope with nitrogen (N) fluctuation in the soil and maintain growth despite changes in external N availability. Nitrate is the most important N form in temperate soils. Nitrate uptake by roots and its transport at the whole-plant level involves a large panoply of transporters and impacts plant performance. Four families of nitrate-transporting proteins have been identified so far: nitrate transporter 1/peptide transporter family (NPF), nitrate transporter 2 family (NRT2), the chloride channel family (CLC), and slow anion channel-associated homologues (SLAC/SLAH). Nitrate transporters are also involved in the sensing of nitrate. It is now well established that plants are able to sense external nitrate availability, and hence that nitrate also acts as a signal molecule that regulates many aspects of plant intake, metabolism, and gene expression. This review will focus on a global picture of the nitrate transporters so far identified and the recent advances in the molecular knowledge of the so-called primary nitrate response, the rapid regulation of gene expression in response to nitrate. The recent discovery of the NIN-like proteins as master regulators for nitrate signalling has led to a new understanding of the regulation cascade